SURVEILANS EPIDEMIOLOGI PENYAKIT DEMAM BERDARAH DENGUE (DBD) DI PUSKESMAS SUNGAI RAYA KABUPATEN INDRAGIRI HILIR - Ikhtiyaruddin Ikhtiyaruddin; Agus Alamsyah; Muhamadiah Muhamadiah; Yuyun Priwahyuni; Christine Vita Gloria Purba (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2020)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus and transmitted by the Aedes aegypti mosquito, which has a sudden fever of 2 to 7 days without a clear cause, weakness / lethargy, restlessness, hearDBDurn, signs of bleeding on the skin in the form of bleeding spots (petechiae, bruises (echymosis) or rash (purapura). The purpose of this study was to determine the implementation of epidemiological surveillance of Dengue Hemorrhagic Fever (DHF) at Sungai Raya Public Health Center in 2020. This type of research is qualitative with a case study approach aimed at monitoring activities surveillance at the Sungai Raya Community Health Center, Indragiri Hilir Regency in 2020. The informant selection technique is purposive sampling with the key informant of the Head of the Community Health Center, the main informant of the DHF program holder and the person in charge of surveillance. Data analysis uses triangulation of sources. sufficient, the accuracy of the diag assessment value is ba ik, the completeness and accuracy of data delivery has good value, good public access. The conclusion of this research is that the implementation of DHF surveillance system is not optimal yet in Sungai Raya Health Center. It is recommended that Sungai Raya Puskesmas be able to make efforts for DHF program holders to take part in surveillance-related training as an effort to increase competence or expertise related to the implementation of DHF training at the Puskesmas.